Продуктивність рослин видів роду Astragalus L. в умовах інтродукції в Правобережному Лісостепу України - Bondarchuk, O.P.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to study peculiarities of productivity of the seeds and aboveground phytomass of plants of the genus Astragalus L. species depending on species and vegetation conditions of the introduction into Right-Bank of Forest- Steppe of Ukraine. Material and methods. The subject of the study was perennial plants of the genus Astragalus species. Investigations were conducted in 2013–2016 years on introduction plots of department of crops flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine in compliance with generally accepted techniques. Processing results of research performed by analysis of variance and statistical estimate of the average data using of program Microsoft Excel (2010). Results. It is established that A. galegiformis L., A. cicer L., A. glycyphyllos L., A. ponticus Pall. and A. falcatus Lam. at introduction into Right-Bank of Forest-Steppe of Ukraine are characterized by high productivity of above-ground phytomass (4,5–13,0 kg/m2), qualitative and quantitative composition, as well as a long ontogenetic period, multifaceted, indicates the profitability of cultivation as a source material for selection studies and use in crop production, which will expand the potential resource base plants of traditional medicine and biofuels and others. Conclusions. It is found that introduced species studied in a culture characterized by high performance, which for years is gradually increasing. The highest productivity (green phytomass and seeds) for all the years of research is recorded in cultur phytocenosis of A. galegiformis.